2004
DOI: 10.1016/j.msea.2003.10.209
|View full text |Cite
|
Sign up to set email alerts
|

The influence of processing variables on the structure and mechanical properties of nano-quasicrystalline reinforced aluminium alloys

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 6 publications
7
30
0
Order By: Relevance
“…4) show the copious presence of near spherical precipitates into the Al matrix. As it was shown in previous work (Todd et al, 2004), x-ray diffraction patterns of the powder showed mainly signal of the α-Al phase together with peaks indexed as an icosahedral phase, i-phase, by using the indexation scheme for icosahedral quasiperiodic crystals (Bancel et al, 1985). In the 25-50 and 50-100 μm powder particle size ranges, some smaller peaks corresponding to the intermetallic Al 23 Ti 9 were also identified.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…4) show the copious presence of near spherical precipitates into the Al matrix. As it was shown in previous work (Todd et al, 2004), x-ray diffraction patterns of the powder showed mainly signal of the α-Al phase together with peaks indexed as an icosahedral phase, i-phase, by using the indexation scheme for icosahedral quasiperiodic crystals (Bancel et al, 1985). In the 25-50 and 50-100 μm powder particle size ranges, some smaller peaks corresponding to the intermetallic Al 23 Ti 9 were also identified.…”
Section: Resultssupporting
confidence: 75%
“…As has been seen above, the QC phase present in the alloy studied in this work is quite stable, and thus, it would contribute to the high mechanical properties of this alloy at high temperatures (Chlup et al, 2003;Galano et al, 2009a;Todd et al, 2004). Effectively, Fe and Cr are quasicrystal formers in Al base alloys, and Ti produces a significant refinement of the icosahedral particle size as well as an increase of the stability (Galano et al, 2004).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…We assess to what extent the ''conventional'' RS (10 3 to 10 5 K/s) microstructure of this alloy is compromised by the slower average cooling rate in spray forming (10 1 to 10 3 K/s), and whether the resultant mechanical properties-available in bulkoffer encouragement for the spray forming of this class of alloy. Al-3Fe-2Cr-2Ti provides a useful benchmark alloy since it has been produced elsewhere by suction casting, [6] RS of powders followed by consolidation, [7][8][9] and MA of powders followed by consolidation. [10][11][12] …”
Section: Introductionmentioning
confidence: 99%